2017
DOI: 10.1007/s00280-017-3476-5
|View full text |Cite
|
Sign up to set email alerts
|

The extent of ground-glass attenuation is a risk factor of chemotherapy-related exacerbation of interstitial lung disease in patients with non-small cell lung cancer

Abstract: The GGA area on HRCT is a risk factor for chemotherapy-related AE-ILD. Therefore, this parameter can be used to predict the risk of AE-ILD before administering chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Previous studies determined that the presence of GGAs, not including brotic area, was a risk for conventional chemotherapy and immunotherapy-related ILD (15,16,22). We also found that the presence of non-brotic ILAs was an independent risk factor for early-onset ICI-ILD.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies determined that the presence of GGAs, not including brotic area, was a risk for conventional chemotherapy and immunotherapy-related ILD (15,16,22). We also found that the presence of non-brotic ILAs was an independent risk factor for early-onset ICI-ILD.…”
Section: Discussionsupporting
confidence: 67%
“…We also found that the presence of non-brotic ILAs was an independent risk factor for early-onset ICI-ILD. GGA re ects in ammation by lymphocytes in the interstitium, and ICIs exert antitumor effects via activation of lymphocytes (15,16,22). These results may explain why GGAs were involved with ICI-ILD (15,16,22).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the % FVC of all patients enrolled in the present study was over 80%, and the % FVC was not a risk factor associated with AE-ILD. Recent reports have shown that the size of the pre-ILD area on pretreatment CT was a risk factor for chemotherapy-related lung injury in patients with both NSCLC and pre-ILD (5,17). However, the extent of pre-ILD in all cases in the present study was mild, and whether or not it was risk factor for AE-ILD could not be determined.…”
Section: Discussioncontrasting
confidence: 66%
“…In China, studies of KL-6 have mainly focused on significant increases in the serum levels of this antigen in the context of different types of ILDs, including IPF, CVD-IP, and HP, and the results have suggested the potential diagnostic use of this parameter. In other countries, researchers have reported distinctly elevated serum KL-6 levels in patients diagnosed with IIP, radiation pneumonitis, pulmonary alveolar proteinosis, CTD-related interstitial pneumonia, non-small cell lung cancer, bronchopulmonary dysplasia in preterm infants, and neonatal high-permeability pulmonary oedema (14)(15)(16)(17). Our observation of significantly higher serum KL-6 levels in patients with IIP relative to those in patients with other lung diseases agreed with the findings of Kohno and Vij (11,18).…”
Section: Discussionmentioning
confidence: 99%